Behavioural and electrophysiological analyses of written word processing in spoken and literary Arabic: New insights into the diglossia question. (4th August 2022) - Andria, Samer; Madi‐Tarabya, Bahaa; Khateb, Asaid
Abstract: Diglossia in Arabic describes the existence and the use of two varieties of the same language: spoken Arabic (SA) and literary Arabic (LA). SA, the dialect first spoken by Arabic native speakers, is used in non‐formal situations for everyday conversations, and varies from one region to another in the Arabic world. LA, acquired later in life when the children learn to read and write at school, is used for formal purposes such as media, speeches in public and religious sermons. Previous research showed that, in the auditory modality, SA words are processed faster than LA ones. In the visual modality, written LA words are processed faster than SA ones, the latter comparing with low‐frequency words. This study analysed event‐related potentials (ERPs) during the processing of high‐frequency (LAHF), LA low‐frequency (LALF) and SA high‐frequency words (SAHF) in a visual lexical decision task. Faster reaction times were observed for LAHF, followed by SAHF and then by LALF. ERPs showed a modulation of the early components starting from the P100 component and of the late P600 component, supposedly related to memory processes. These findings, indicating that processing written SAHF words was largely comparable with processing of LALF, are discussed in the context of Arabic diglossia. Abstract : Arabic diglossia refers to the use of a two varieties (spoken and a literary Arabic), which some authors consider as a form of bilingualism. The processing of written spoken and literary Arabic words was analysed using behavioural and ERP measures. Processing written spoken words compared to processing low but not high‐frequency literary words. This study is the first to monitor the time course of word processing in Arabic, and the results provide new insights into the neural basis of diglossia.